2014
DOI: 10.1056/nejmoa1307095
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations inAPOC3,Triglycerides, and Coronary Disease

Abstract: Background Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. Methods We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
378
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 920 publications
(392 citation statements)
references
References 38 publications
11
378
0
3
Order By: Relevance
“…Recent Mendelian randomization studies suggested a prominent role of apoCIII activity in atherosclerotic disease by evaluating the effects of lifelong exposure to genetically reduced apoCIII function and reduced TG levels 14, 15. apoCIII is an integral component of RLPs and inhibits the function of lipoprotein lipase and hepatic lipase, while potentially promoting VLDL assembly 44, 45.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent Mendelian randomization studies suggested a prominent role of apoCIII activity in atherosclerotic disease by evaluating the effects of lifelong exposure to genetically reduced apoCIII function and reduced TG levels 14, 15. apoCIII is an integral component of RLPs and inhibits the function of lipoprotein lipase and hepatic lipase, while potentially promoting VLDL assembly 44, 45.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, some studies have suggested that this association is attenuated by the inclusion of other potentially causal factors such as HDL‐C, thus raising the question of whether RLPs may represent a surrogate for other causative factors in atherosclerotic disease 12, 13. Recent Mendelian randomization studies have served as the strongest evidence that RLPs are etiologic for atherosclerosis 6, 14, 15, 16. Further, TGs are predictive of residual risk in statin‐treated individuals 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of noninvasive vascular imaging techniques have been shown to improve cardiovascular risk prediction 38. Newer evidence from large genetic studies39, 40 indicates that triglycerides, the culprit of atherogenic dyslipidemia,41 is causally related to future CVD events, and triglyceride lipoprotein content has been associated with preclinical atherosclerosis 42. Triglycerides, as well as high‐density lipoprotein cholesterol, may contribute to residual cardiovascular risk beyond LDL cholesterol levels 43, 44.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on susceptibility factors contributing to an increased risk 1 , while only few studies have identified protective variants conferring reduced risk. Recently, the TG and HDL Working Group and Jørgensen et al reported that loss-of-function mutations in APOC3 are associated with decreased triglyceride levels and a reduced risk of ischemic vascular disease in individuals of European and African ancestry 2, 3 . Approximately 1 in 150 individuals were heterozygous carriers of at least one of the four mutations: R19X, A43T, IVS2+1G→A, and IVS3+1G→T.…”
Section: Correspondencementioning
confidence: 99%